Pendidikan Akhlak Bermasyarakat Dalam Perspektif Hadis Nabi - Rohmansyah (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
This research aims to describe and provide concrete explanations about how the Prophet Muhammad provide moral education in hanging out and wrestle in public life. Reseach library research methods with the collection of data was descriptive-intepretatif. The results of this research in the study of the Hadith are: first, to drop by and receive the guests. Second, establish good relations with the neighbours namely mutual say greetings and respond when encountering each other, looked out the person being sick, complementary invitation if not hitch, delivering bodies came to the liang lahat and answer the person who sneezes. Third, build social piety to his fellow man. Fourth, establish ukhuwah islamiyah with fellow human beings. The fourth thing that when developed it will create a social life that is dignified and appropriate grain berkeadaban pancasila first until the fifth sila sila. By the way, because the values of community morals education in the word Hadith the Prophet could provide inspiration and motivation to continually do tajdīd (renewal) of good character at the center of public life. Moral education of community implies to all existence of Islam in all his teaching either can the Qur'an nor Hadith the Prophet, either about the creed, worship and mu'amalah as political, economic and others. In addition, forming a disciplined man, leading to emotional intelligence and spiritual, wise, brave, keep yourself and be fair.